2016
DOI: 10.1002/jso.24465
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic follow‐up of untreated enchondroma and atypical cartilaginous tumors in the long bones

Abstract: Background and ObjectivesBoth enchondroma and atypical cartilaginous tumors (ACT) are not considered malignant, so inactive and asymptomatic tumors might not need surgery. To the best of our knowledge, this is the first study that has been done to evaluate the natural course of conservative‐treated enchondroma and ACT in the long bones.MethodsFor this retrospective study, we analyzed the results of patients in whom we refrained from surgery and only regularly performed radiological follow‐up of the tumor. Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 26 publications
1
84
0
3
Order By: Relevance
“…In 49 patients with conservatively treated ECs and ACTs of long bones, implementing follow-up imaging with radiographs and MRI, Deckers et al noticed that only 6% of the patients underwent surgical treatment during follow-up (due to invalidating pain or radiologic growth). 3 None of the surgically treated lesions had transformed into a higher grade CS, suggesting that surgery indication should be evaluated more scrupulously. Furthermore, the duration of follow-up time before surgery had no impact on the procedure itself or on the patient's rehabilitation.…”
Section: Follow-up: the Other Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 49 patients with conservatively treated ECs and ACTs of long bones, implementing follow-up imaging with radiographs and MRI, Deckers et al noticed that only 6% of the patients underwent surgical treatment during follow-up (due to invalidating pain or radiologic growth). 3 None of the surgically treated lesions had transformed into a higher grade CS, suggesting that surgery indication should be evaluated more scrupulously. Furthermore, the duration of follow-up time before surgery had no impact on the procedure itself or on the patient's rehabilitation.…”
Section: Follow-up: the Other Questionmentioning
confidence: 99%
“…Evidence shows that $ 4% of solitary ESs can change into CSs, and a small subset of ECs may regress while most of these lesions will remain unchanged, highlighting the need for follow-up. 3,7 Radiographic follow-up instead of surgery may prevent overtreatment, resulting in less morbidity and lesser costs. We recommend that every chondroid lesion characterized by the absence of imaging and clinical signs of malignancy in a long bone should have planned interval follow-up.…”
Section: Follow-up: the Other Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent natural history study of these tumors, Deckers and colleagues [2] found that only 6% of their patients with hyaline cartilage tumors required operation for ''medical reasons'' (tumor growth or unexplained pain). Why are so many of these lesions in need of biopsy?…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Only a small percentage of long bone hyaline cartilage tumors require surgery [2]. If we could agree to use behavior as the gold standard, the key in developing a standardized approach to these tumors would then be to develop a nomogram based on clinical and radiologic criteria.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%